Development of hepatitis B virus capsids into a whole-chain protein antigen display platform: new particulate Lyme disease vaccines - Nassal, Michael; Skamel, Claudia; Vogel, Maren; Kratz, Peter A.; Stehle, Thomas; Wallich, Reinhard; Simon, Markus M. (International journal of medical microbiology, 2008)
The immunogenicity of peptides and small protein fragments can be considerably enhanced by their presentation on particulate carriers such as capsid-like particles (CLPs) from hepatitis B virus (HBV). HBV CLPs are icosahedral nanoparticles formed by 90 or 120 core protein dimers. Insertions into the immunodominant c/e1 B cell epitope, a surface-exposed loop on the HBV capsid protein, are especially immunogenic. Here we investigated whether the HBV core protein can be exploited as a vaccine carrier for whole-chain protein antigens, using two clinically relevant proteins derived from a bacterial human pathogen, the Lyme disease agent Borrelia burgdorferi. For this purpose we analyzed CLP formation by core fusions with the entire 255-amino-acid ectodomain of outer surface lipoprotein A (OspA), and with two distinct, 189 amino acid long variants of the dimeric OspC (OspC(a), OspC(b)) of B. burgdorferi. OspA appropriately inserted into the HBV core protein yielded a multimerization-competent fusion protein, termed coreOspA. Although only partially assembling into regular CLPs, coreOspA induced antibodies to OspA, including the Ig isotype profile and specificity for the protective epitope "LA-2", with an efficiency similar to that of recombinant lipidated OspA, the first generation vaccine against Lyme disease. Moreover, coreOspA actively and passively protected mice against subsequent challenge with B. burgdorferi. Fusions with the two OspC variants were found to efficiently form regular CLPs, most probably by OspC dimerization across different core protein dimers. In mice, both coreOspC preparations induced high-titered antibody responses to the homologous but also to the heterologous OspC variant, which conferred protection against challenge with B. burgdorferi. The data demonstrate the principal applicability of HBV CLPs to act as potent immunomodulator even for structurally complex full-length polypeptide chains, and thus open new avenues for novel vaccine designs.